Hukum Antidumping di Indonesia dari Perspektif Ketahanan Industri Dalam Negeri - Yulianto Syahyu, Yulianto Syahyu (Jurnal Keamanan Nasional, 2019)
The protection of the resilience of the domestic industry today is haunted by the practice of dumping by exporting countries of goods and services. Dumping is a competition practice between countries where the selling price of imported goods is below the normal price of good/services in the country. The practice of dumping is carried out by the exporting country by determining the price below or lower than the nominal value or the actual unit cost or can also be said to sell at a lower price in the importing country than in the producer country itself This is certainly detrimental to local businessmen and laborers in the country so that regulations from importing recipient countries are needed for the resilience of the domestic industry in order to sustain the national economy. Some exporting countries often practice dumping to increase the economic benefits of the country itself but can harm the importing country. To avoid this dumping practice, Indonesia’s anti-dumping laws has an important role in the concept of domestic industry resilience.